Framing Media Dan Dinamika Opini Publik TerkaitPengungsi Rohingya Di Indonesia: Perspektif UNHCR Dan Otoritas Aceh Dalam Sorotan Kritis - Mamis, Subria; Rustan, Ahmad Sultra; Arnus, Sri Hadijah; Basri, Hasan (Wardah, 2023)
This research analyzes media framing regarding the rejection and acceptance of Rohingya as refugees in Indonesia. The research focuses on the framing of news coverage issued by UNHCR and the Aceh District Government, as well as other media that explicitly voice rejection of the presence of the Rohingya. Content analysis was used as the main approach to investigate how this issue was presented and further explored in the media so that differences in media were observed in depicting this topic. The research results show that UNHCR views the Rohingya as an entity that has the right to be welcomed in Aceh, based on Human Rights principles and the belief that their presence will not exploit conditions in Aceh. On the other hand, the news framing that rejects the presence of the Rohingya comes from justification for Indonesia's non-participation in signing the refugee convention, which is interpreted as the basis that Indonesia is not obliged to accept the Rohingya. The Aceh Regional Revenue and Expenditure Budget allocation for handling the flood disaster strengthens the reasons for rejection, accompanied by firm demands from the Aceh District Government for the Indonesian government to respond to this policy. The urgency of this research lies in the need for an in-depth understanding of the dynamics of media framing which can shape public opinion and influence government policy regarding humanitarian issues in local, regional, and even international contexts.